Cellular imbalance of specific RNA-binding proteins associates with harmful R-loops. - José Antonio Mérida-Cerro; Guillaume Chevreux; Benoit Palancade; Ana G Rondón; Andrés Aguilera (PLoS Genetics)
Understanding how the assembly of nascent mRNA into a ribonucleoprotein (mRNP) influences R-loop homeostasis is crucial for gaining insight into the cellular mechanisms that prevent genome instability. Here, we identify three RNA-binding proteins, Rie1, Rim4 and She2, whose expression levels are important to limit R-loop accumulation and, thus, to prevent DNA damage. Interestingly, Rim4 and She2 are overrepresented in CBP80-containing mRNPs formed in the absence of THO. In addition, we found that an excess of the RNA exosome component Dis3 impairs its function, promoting R-loops, particularly from non-coding RNAs, which cause genomic instability. Our results indicate that changes in the availability of different RBPs or RNAs, causes R-loop-mediated DNA damage in the cell. These results may help to understand the mechanism that promotes cancer, as several RBPs are overexpressed in different types of tumors.